Decentering the master discourse and locating the continuity of Indianness in Rani Manicka's 'The Rice Mother' and 'The Japanese Lover' - Krishnarajah, Suvinamalar (2013)
The British occupation of Malaya was an ideological apparatus in the guise of nationalism that was used to politicise identity through racial consciousness and the politics of education. Although this idea was the primary concern of many early Malaysian Literature in English (MLlE) writers such as K. S. Maniam and Lloyd Fernando, this study instead examines the politicisation of identity brought about by the Japanese occupation of Malaya during World War II. In doing so, the study focuses on the human suffering wrought by this occupation, as seen through the perspective of Indian families who lived through the war. In other words, the study examines the decentering of the master discourse (against the enduring significance of British occupation on Malaysia) and traces the location and continuity of Indianness in two novels by the diasporic Malaysian Indian writer Rani Manicka, namely The Rice Mother (2002) and The Japanese Lover (2010). The respective protagonists and settings of both novels, in which the Japanese occupation becomes the primary discourse, are situated within the framework of poststructural feminism and postcolonialism so as to explore changing thematic patterns and the continuity of Indian religious beliefs, philosophy and customs impacted by the era of colonisation. Both The Rice Mother and The Japanese Lover are also read using a hermeneutical approach; that is, in cognisance of the fact that Manicka is writing within a definite historical context-the context of MLIE and a nationalistic narrative which tends to downplay the significance of the Japanese occupation on the formation of the Malaysian Indian cultural identity. The study also examines how Manicka, through these two novels, challenges unceasing patriarchal and colonial bias. The study finds that Manicka 'completes' Maniam's narrative by not only having her characters avoid the trap of transcendental escapism into a mythological past, but also by sublating the consciousness of their ethnic past into a wider political consciousness.